Effect of supplemental β‐carotene compared to retinyl palmitate on fatty acid profile and expression of mRNA from genes involved in vitamin A metabolism in beef feedlot cattle. (30th March 2017) - Condron, Kaitlin N.; Waddell, Jolena N.; Claeys, Matt C.; Lemenager, Ronald P.; Schoonmaker, Jon P.
Abstract: To examine the effects of dietary β‐carotene (βC) or retinyl palmitate (RP) on fatty acid (FA) profile and mRNA expression, samples were collected from 24 Angus‐cross calves that were allotted to four treatments consisting of RP supplemented at 2200 IU/kg, and synthetic β‐carotene (SβC) supplemented at one, five or 10 times RP. Longissimus muscle (LM) cis ‐9, trans ‐11 conjugated linoleic acid was greater in RP compared to SβC1X ( P = 0.04). The polyunsaturated:saturated FA increased linearly ( P = 0.04) in the LM as dietary SβC increased. Expression of βC oxygenase 2 ( βCO2 ), an enzyme that cleaves β ‐carotene, was greater in the LM for SβC1X compared to RP and decreased linearly as SβC increased (P ≤ 0.02). Peroxisome proliferator activated receptor γ (PPARγ ) expression in the LM increased in SβC1X compared to RP ( P = 0.03); however, PPARγ and retinoic acid X receptor α ( RXRα) expression decreased linearly ( P = 0.02) in the LM with increasing SβC. Retinoic acid receptor α ( RARα) expression tended ( P = 0.10) to decrease linearly in the LM with increased SβC. In conclusion, SβC supplementation increased mRNA expression of some lipogenic genes in the LM, but increasing dietary SβC inhibited their expression and tended to increase polyunsaturated FA.